Answer:
see below
Step-by-step explanation:
(2x + i)(2x – i)
FOIL
first 2x*2x =4x^2
outer -i * 2x = 2x i
inner i * 2x = 2x i
last i * -i = -i^2 and i^2 = -1 so - (i^2 ) = - (-1) = 1
Add together
4x^2 + 2xi -2x i +1
Combine like terms
4x^2 +1
Answer:
Step-by-step explanation:
That would be 0=12 or 10 so that means you have to add 2 to 10.
The property used is the Associative property
3 × 70 = 3(70) = 3 (7×10) = (3×7) ×10
The formula is
a × bc = a (bc) = a (b×c) = (a×b) ×c
Its 1.33 because you round up if its 5 or greater